2017
DOI: 10.1017/s1049023x17005544
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Lifestyle Behaviors of University Students

Abstract: person. What is witness event doing? What are the main causes of absence of first aid? Background: The ability of carrying out first aid should be one of basic skills in each of us. Methods: The study was conducted in the third quarter of 2015, on 335 members of emergency medical teams: doctors, paramedics, nurses and drivers, who provided medical rescue activities in the Provincial Ambulance and Health Transport "Meditrans" in Warsaw. The research tool was an anonymous questionnaire. Results: The straight maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Arpağ et al (2020) found that students with a higher income received higher scores in the physical activity subscale than those with lower income. Recent studies determined that HPLP-II total and subscale mean scores of students statistically significantly increased with their level of economic status (Çalışkan, Arberk & Üner, 2017).…”
Section: Discussion Of Findings Associated With Healty Life-style Rou...mentioning
confidence: 99%
“…Arpağ et al (2020) found that students with a higher income received higher scores in the physical activity subscale than those with lower income. Recent studies determined that HPLP-II total and subscale mean scores of students statistically significantly increased with their level of economic status (Çalışkan, Arberk & Üner, 2017).…”
Section: Discussion Of Findings Associated With Healty Life-style Rou...mentioning
confidence: 99%
“…For most people, this is the beginning of independent life. Many people then change their place of residence; family relations and old acquaintances are lost, and completely new relationships are created, which may result in a specific environment, perpetuating wrong habits and an irregular lifestyle [ 5 , 7 ]. While studying at universities, there may be many dangers related to the potential risk of addiction, inadequate diet, lack of exercise, and inadequate coping with stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies on this subject so far have focused on single health behavior. The verification of the intensity of several health practices is less frequent [ 4 , 5 ], although it is essential for the assessment of the lifestyles of the populations studied. Given the above, questionnaires such as Health Behavior Inventory were developed, which aimed to collect general information on the intensity of health behaviors and their basic categories [ 6 ].…”
Section: Introductionmentioning
confidence: 99%